2017
DOI: 10.21527/2176-7114.2017.32.5-14
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Xerostomia Em Pacientes Com Câncer De Cabeça E Pescoço Submetidos Ao Tratamento Radioterápico

Abstract: RESUMOObjetivo: avaliar a relação entre a xerostomia e a qualidade de vida dos pacientes com câncer de cabeça e pescoço submetidos ao tratamento radioterápico. Metodologia: Estudo prospectivo do tipo caso-controle, desenvolvido no Hospital Ophir Loyola, com amostra constituída de 20 pacientes. A pesquisa foi desenvolvida em duas etapas, antes e após a radioterapia, com aplicação de um formulário próprio, questionário QLQ-H&N35 e a aplicação da sialometria espontânea. Para análise dos dados utilizou-se o Micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
2
1
0
2
Order By: Relevance
“…This considerable decrease demonstrates that, although none of the analyzed patients underwent surgical excision of the salivary glands, the treatment of choice may have caused indirect injury to the salivary glands, which resulted in a reduction in SFV during the treatment period. This result is similar to that of a study by Silva et al (2017) 19 who, using the technique of spontaneous sialometry, found that reduced salivary flow before radiotherapy was present in 35% of 20 patients, and 100% of the patients had some degree of reduction in salivary flow at the end of radiotherapy. It is noteworthy that in the present study, SFV was evaluated using stimulated saliva.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This considerable decrease demonstrates that, although none of the analyzed patients underwent surgical excision of the salivary glands, the treatment of choice may have caused indirect injury to the salivary glands, which resulted in a reduction in SFV during the treatment period. This result is similar to that of a study by Silva et al (2017) 19 who, using the technique of spontaneous sialometry, found that reduced salivary flow before radiotherapy was present in 35% of 20 patients, and 100% of the patients had some degree of reduction in salivary flow at the end of radiotherapy. It is noteworthy that in the present study, SFV was evaluated using stimulated saliva.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, they found that hyposalivation persisted for up to six weeks post--radiotherapy. Similar to the studies by Silva et al (2017) 19 and Lima et al (2004) 10 , in the present study, the daily dose of irradiation was 200 cGy, and although the final treatment dose varied, it was always > 4,000 cGy; therefore, it was capable of causing permanent damage to the salivary glands 20 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Silva et al 25 avaliaram a relação entre a xerostomia e a qualidade de vida relacionada à saúde bucal em pacientes com câncer de cabeça. Os resultados apontaram alta prevalência no sexo feminino (85%), com idades entre 51 e 70 anos (40%), frequentemente diagnosticadas com câncer de cabeça e pescoço.…”
Section: Discussionunclassified
“…O diagnóstico é realizado através de inspeção da mucosa oral e pela sialometria, um teste muito efetivo que busca identificar o fluxo salivar. O tratamento é paliativo e consiste na estimulação da saliva do paciente (BARBIERI; COSTA; GUERRA, 2020;SILVA et al,2017).…”
Section: Abordagem E Tratamento Das Manifestações Orais Em Decorrência Daunclassified